The Effect of an Emergency Department Dedicated Midtrack Area on Patient Flow. (April 2014) - Soremekun, Olanrewaju A.; Shofer, Frances S.; Grasso, David; Mills, Angela M.; Moore, Jessica; Datner, Elizabeth M.; Griffey, Richard T.
Abstract Background Emergency department (ED) crowding negatively affects quality of care and disproportionately affects medium‐acuity (Emergency Severity Index [ESI] level 3) patients. The effect of a dedicated area in the ED focused on these patients has not been well studied. Objectives The objective was to find out the operational effect of a midtrack area dedicated to the evaluation and safe disposition of uncomplicated medium‐acuity (ESI 3) patients. Methods This was a 24‐month pre‐/postintervention study to evaluate the effect of implementation of a dedicated midtrack area at an urban tertiary academic adult ED. The midtrack had three examination rooms and three hallway stretchers for ongoing treatment staffed by an attending physician and two registered nurses (RNs). Besides the two additional RNs representing a 3.4% increase in total daily nursing hours, the intervention required no additional ED resources. The midtrack area was open from 1 p.m. to 9 p.m. on weekdays, corresponding to peak ED arrival rates. All patients presenting during weekdays were included, excluding patients triaged directly to the trauma bay or psychiatric unit or who expired in the ED. The main outcomes were left without being seen (LWBS) rates and ED length of stay (LOS), adjusting for patient volume, daily total patient hours (a proxy for ED crowding), and acuity. Results A total of 91, 903 patients were included for analysis during the study period including 261 pre‐ and 256 postintervention days. Comparing the pre‐ and postintervention periods, mean ED daily visits (173 vs. 182) and mean total daily patient hours (889 vs. 942) were all significantly higher in the postintervention period (p < 0.0001). There was no significant change in percentage of patients with high triage acuity levels. Despite this increase in volume and crowding, the unadjusted and adjusted LWBS rates decreased from 6.85% to 4.46% (p < 0.0001) and from 7.33% to 3.97% (p < 0.0001), respectively. The mean LOS for medium‐acuity patients also decreased by 39.2 minutes (p < 0.0001). For high‐acuity patients, there was no significant change in the mean time to room (14.69 minutes vs. 15.21 minutes, p = 0.07); however, their mean LOS increased by 24 minutes (331 minutes vs. 355 minutes, p < 0.0001). Conclusions Implementation of a midtrack area dedicated to caring for uncomplicated medium‐acuity (ESI 3) patients was associated with a decrease in overall ED LWBS rates and ED LOS for medium‐acuity patients.